Environmental Status of Italian Coastal Marine Areas Affected by Long History of Contamination - Ausili, Antonella; Bergamin, Luisa; Romano, Elena (Frontiers in Environmental Science, 2020)
In the first decades of 2000s, several Italian sites affected by strong anthropogenic impact were recognized as “Site of National Interest” (SIN) for a successive reclamation project, some of which also including marine sectors. These coastal areas are characterized by high complexity and diversity as regards the natural setting as well as for extent, history and type and degree of contamination. For this, the Italian Ministry of Environment charged its scientific research Institute (earlier ICRAM, now ISPRA) with planning a flexible, adaptable and large-scale environmental characterization. In this context, the investigation of marine sediments was identified as the primary target to assess the environmental status, because of their conservative capacity with respect to contaminants and their role in the exchange processes with other environmental matrices, such as water column and aquatic organisms. A multidisciplinary, chemical-physical and ecotoxicological survey was identified as the most appropriate and objective criterion for assessing the sediment quality associated, when necessary, with integrative studies. The results derived from this multidisciplinary approach highlighted the main sources of contamination, together with size and extent of the environmental impact on the coastal marine areas, strictly correlated with the kind of anthropogenic activities and coastal morphology. In order to underline how the different environmental setting influence the degree of anthropogenic impact, 4 different case studies, selected among the more complex by geochemical and geomorphological viewpoint and more extensively studied, were considered. A comprehensive evaluation of these case studies allowed to deduce some general principles concerning the effects of anthropogenic impact, which can be applicable to other transitional and marine coastal areas.